Akuntansi Forensik dan Audit Investigatif dalam Pengungkapan Fraud - Dewi Anggraini; Eri Triharyati; Helen Anggia Novita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
Forensic accountants are tasked with providing legal opinions in litigation. Besides that, there is also the role of forensic accountants in the field of law outside the court (non-itigation) for example in helping to formulate alternative settlement cases in disputes, formulation of compensation calculations and efforts to calculate the impact of termination / breach of contract. Investative audit, a form of audit or examination that aims to identify and uncover fraud or crime by using approaches, procedures and techniques commonly used in an investigation or investigation into a crime. Because the purpose of an investigative audit is to identify and disclose fraud or crime, the approaches, procedures and techniques used in investigative audits are relatively different from the approaches, procedures and techniques used in financial audits, performance audits or audits with other specific objectives. In an investigative audit, an auditor initiates an audit with presumptions / indications of possible fraud and crimes that will be identified and revealed through the audit to be carried out. Such conditions, for example, will affect who will be interviewed in advance or what documents must be collected first. In addition, in an investigative audit, if it has authority, the auditor can use procedures and techniques commonly used in the investigation and investigation of crimes, such as surveillance and searches. Fraud is the process of making, adapting, imitating or objects, statistics, or documents, with the intent to cheat. But we can prevent fraud and we can avoid fraud is very detrimental to various parties because it can destroy government and business. Fraud is in the form of corruption in its wider destructive power. Basically the scope of forensic accounting is fraud in the broadest sense. Keywords: Forensic Accounting, Investigative Audit and Fraud